81 Recruiting lay-persons to out-of-hospital cardiac arrests through a smartphone application based response system. (16th April 2018) - Andelius, L; Folke, F; Karlsson, L; Torp-Pedersen, C; Lippert, FK; Kjølbye, JS; Møller, S; Gislason, GH; Hansen, CM
Abstract : Aim: Despite their lifesaving potential, automated external defibrillators (AEDs) are seldom used in out-of-hospital cardiac arrests (OHCAs). Activating lay-persons to transport AEDs to nearby OHCAs holds the potential to increase bystander defibrillation and improve OHCA survival. The 'HeartRunner'-system is a mobile-phone position system which activates lay volunteers through a smartphone application to attend in OHCA resuscitation. We investigated the recruiting process and characteristics of the lay volunteers. Method: From September 1 st 2017, lay-persons have been able to download the 'HeartRunner'-application and register as a lay volunteer in the Capital Region of Denmark comprising 1.8 million inhabitants. Recruiting strategies included advertisements outdoor and in newspapers, e-information, and through nationwide television coverage. Results: During the first four months, 14 935 people registered as lay volunteers (=820/100, 000 inhabitants); 52.3% were male and 28.3% were health care professionals. Median age at registration was 36 years (27–48). In total, 278 suspected OHCAs were registered and 3029 lay volunteers were alerted (mean of 11 volunteers per alarm). Of all alerted lay volunteers, 51.3% (n=1, 554) responded to the alarm and 56.9% (n=884) accepted the mission. Of them, 53.7% were male, 32.0% were health care professionals, and median age was 38 years (27–49). The most effective recruiting strategy was nationwide television broadcast, which recruited nearly 6000 volunteers in one day. Conclusion: Lay-persons can be recruited through a smartphone application based response system, and a high proportion accepts to volunteer as first responder in OHCA resuscitation. Conflict of interest: None Funding: Dr. L. Andelius is supported by a fund from The Danish foundation TrygFonden, who has no influence on study design; in the collection, analysis, or interpretation of data.